The Limits of Bookland. (23rd December 2020) - Blair, John
ABSTRACT: This paper aims to demystify the concept of bookland, and to suggest that it matters less for understanding what was distinctive about early England than historians have often supposed. The first part emphasises diplomas as beneficiary-led symbols of culture and status rather than instruments of royal policy. As the primary monastic context faded during the ninth century, so did the distinctive aspects of bookland. By c. 950, bōcland could translate fundus or simply terra, and thereafter diplomas had little effective function beyond signalling the status of landowner and thegn: bookland was absorbed into straightforward allodial possession. In the second part, it is argued that large areas of eastern England never had lay bookland tenure at all, though there was a limited extension of diploma use into parts of the east midlands after c. 940. Rather than a homogeneous Anglo-Saxon charter tradition, we should envisage distinct traditions in the south and west reflecting Italian, Frankish and Brittonic influences. Eastern England, by contrast, faced the North Sea, Scandinavia and the Low Countries: like other English regions it had a high monastic culture during c. 670–800, and that could have included diplomas, but its main documentary tradition is likely to have been more vernacular and decentralized.